A fluorescent probe for thiols based on strong nucleophilic attack of sulfhydryl and its bioimaging. Issue 20 (27th August 2015) - Li, Jianfang; Yin, Caixia; Huo, Fangjun; Chao, Jianbin; Zhang, Yongbin; Niu, Lixi
Abstract : The sensor that displayed selectivity for copper ions, as evidenced by a green fluorescence to colorless change, was characterized using fluorescence spectroscopy and its potential application to bioimaging was also illustrated. Abstract : A fluorescent probe has been synthesized and characterized as a selective and sensitive sensor for thiol detection. The probe exhibits a rapid response and high sensitivity to thiols in HEPES : DMF = 1 : 1 (v/v pH = 7.0) solution. The practical utility of the probe was demonstrated by its application to the detection of thiols in living cells.